Longitudinal associations between sleep and anxiety during pregnancy, and the moderating effect of resilience, using parallel process latent growth curve models - van der Zwan Judith Esi; de Vente Wieke; Tolvanen Mimmi; Karlsson Hasse; Buil J Marieke; Koot Hans M; Paavonen E Juulia; Polo-Kantola Päivi; Huizink Anja C; Karlsson Linnea (ELSEVIER SCIENCE BV, 2022)
Background: For many women, pregnancy-related sleep disturbances and pregnancy-related anxiety change as pregnancy progresses and both are associated with lower maternal quality of life and less favorable birth outcomes. Thus, the interplay between these two problems across pregnancy is of interest. In addition, psychological resilience may explain individual differences in this association, as it may promote coping with both sleep disturbances and anxiety, and thereby reduce their mutual effects. Therefore, the aim of the current study was to examine whether sleep quality and sleep duration, and changes in sleep are associated with the level of and changes in anxiety during pregnancy. Furthermore, the study tested the moderating effect of resilience on these associations.
Methods: At gestational weeks 14, 24, and 34, 532 pregnant women from the FinnBrain Birth Cohort Study in Finland filled out questionnaires on general sleep quality, sleep duration and pregnancy-related anxiety; resilience was assessed in week 14.
Results: Parallel process latent growth curve models showed that shorter initial sleep duration predicted a higher initial level of anxiety, and a higher initial anxiety level predicted a faster shortening of sleep duration. Changes in sleep duration and changes in anxiety over the course of pregnancy were not related. The predicted moderating effect of resilience was not found.
Conclusions: The results suggested that pregnant women reporting anxiety problems should also be screened for sleeping problems, and vice versa, because women who experienced one of these pregnancy-related problems were also at risk of experiencing or developing the other problem. (C) 2017 Elsevier B.V. All rights reserved.